Analysis of Microbial Contamination of Drinking Water in Peshawar - Ullah, Jamshid; Ullah, Aziz; Afnan; Khan, Umair; Rasool, Muhammad Fawad; Majeed, Abdul; Hussain, Iltaf (Journal of Research (Science), 2025)
Waterborne disease is a major public health problem caused by potentially lethal microorganisms which have serious health implications such as morbidity and death in severe cases. This study aimed to assess the microbiological quality of drinking water in thirteen different urban and rural areas of Peshawar, Pakistan. This cross-sectional study was approved by Khyber medical university Peshawar. A sterile water container was used to collect samples from tap water, distribution network, Tube Wells, and the hand pump by applying standard microbiological techniques. A multiple tube fermentation technique was used to analyze water samples. A total of 100 samples were collected from both urban and rural areas of Peshawar. Of these 22% were not contaminated whereas 78% were contaminated with fecal coliform and E. coli. The Prevalence of coliforms in contaminated water samples (n=78) for total coliforms, fecal coliforms, and E. coli was 34%, 26%, 18% respectively. The range of 2.2-240+/100ml confirmed E. coli count in urban and rural areas were 10% and 12% respectively. The prevalence of potentially deadly pathogens in the study setting indicates poor drinking water quality, which has serious health consequences. Serious attention needs to reduce the occurrence of water-borne diseases in such areas.